UTILIZATION OF COAL GASIFICATION PRODUCER GAS FOR POWER GENERATION USING 10 KW SPARK IGNITION ENGINE - N. Nurhadi; M. Ade A. Efendi (Indonesian Mining Journal, 2016)
Coal gasification is the process of converting coal into gas to ease its use and more environmentally friendly. Research and Development Center for Mineral and Coal Technology (tekMIRA) has been researching, designing, and developing a small-capacity gasifier with the brand of GasMin. This study discusses GasMin design and utilization for power generation using internal combustion engine type spark ignition engine. The result of laboratory analysis shows that the calorific value of producer gas was 1,013 kcal/Nm3, tar content was 4.04 mg/Nm3, particulate content was 11.17 mg/Nm3 and temperature of gas was 36oC. Based on characteristic of producer gas, it can be used for fuel in internal combustion engine. The internal combustion engine generator set (genset) used in this research was 10 kW spark ignition type. To be used for gas producer, some modifications were made on genset engine by replacing the function of the carburetor into mixing chamber for air and producer gas, and placed before mixing gas entering the combustion chamber.The results ofthis researchshow that the power generated was 4.8 kW, which was about 53% of maximum power on fuel. It isin accordance with the literature whichstates that de-rating of the genset engine ranges from 40-50%.